Improving workflow at the Emergency Department – simple lessons from the lean management concepts - Ada Lisowska; Ada Lisowska; Jacek Kleszczyński; Jacek Kleszczyński; Arkadiusz Wilczek; Arkadiusz Wilczek; Grzegorz Wolf; Tomasz Holecki (European Journal of Translational and Clinical Medicine, 2025)
Background: Work in the hospital emergency department (ED) is characterized by a significant (and sometimes excessive) number of patients in relation to medical staff and space and high variability of clinical situations, all in conditions of time deficit. The concept of lean management (LM) may be helpful in solving some of the organizational problems at the ED. One of the tools derived from LM is the 5S method (sort, set in order, shine, standardize and sustain), which serves to organize the workflow, eliminate waste and increase patient safety. Material and methods: In the ED of University Clinical Hospital in Opole (Poland) we used survey methods (questionnaires, direct interviews and group discussions with the participants) to identify the issues that caused the greatest difficulties in the work flow. 3 months after implementing changes, we conducted a survey among the participating ED nurses and paramedics to obtain opinions on the introduced changes. Results: Majority of the participants found the implemented changes (e.g. equipment checklists, standardized equipment and supply placement in all ED areas) ”definitely necessary” and ”rather necessary.” Conclusions: The implementation of LM, particularly the 5S method and checklists, seems to be useful in the organization of work in the ED and was positively assessed by the staff.